RANCANG BANGUN SISTEM INFORMASI STOCK OPNAME BERBASIS WEB DENGAN METODE WATERFALL PADA UMKM - Fauzan Firdaus; Mumu Komaro; Vina Dwiyanti (Jurnal Teknologi Informasi dan Komputer, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, yet they continue to face challenges in inventory management. One of the main challenges is the inaccuracy of stock recording due to the use of manual stock-taking methods, which are time-consuming, prone to errors, and result in inconsistent data. This condition affects business operations, such as overstocking or stockouts, leading to inefficient management and potential financial losses. This study aims to design and develop a Web-Based Stock Opname Information System to improve the accuracy and efficiency of inventory recording in MSMEs. The system development adopts the waterfall method, which consists of several stages: requirements analysis, system design, implementation, testing, and maintenance. Each stage plays a crucial role in ensuring the system aligns with user needs. The web-based system enables real-time stock monitoring, minimizes recording errors, and enhances operational efficiency. Through the implementation of this system, MSMEs are expected to optimize inventory management, reduce human error, and improve competitiveness in facing increasingly complex business challenges.